Sovereign equality and moral disagreement premises of a pluralist international legal order - Roth, Brad R. (New York ; Oxford : Oxford University Press, 2011)
The boundaries of the international order's pluralism remain variable, & relative convergences in both values & interests over time have led to the broadening of exceptions to sovereign prerogative, such as jus cogens, universal jurisdiction, and humanitarian intervention. This book discusses this topic.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sovereignty; Equality of states; United Nations